2023
DOI: 10.1111/jan.15747
|View full text |Cite
|
Sign up to set email alerts
|

A divided community: A descriptive qualitative study of the impact of the COVID‐19 pandemic on nurses and their relationships

Abstract: AimsTo identify the personal and professional impact of the COVID‐19 pandemic on clinical nurses with regard to personal and workplace safety, personal and professional relationships and perceptions of their team, organization and community, and to understand lessons learned to inform future responses to pandemics or global emergencies.DesignQualitative, descriptive free‐text surveys, informed by appreciative inquiry.MethodsNurses working in adult COVID‐ and non‐COVID cohort medical‐surgical and intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…There have been many papers written about the effects of the pandemic on the nursing workforce (Jackson, 2022) and we are still in a place of learning from the changes and innovations instigated during the pandemic.However, we do know that nurses experienced many personal and professional stressors because of the COVID-19 pandemic. In a study that aimed to identify the impacts of the pandemic on nurses,Morley et al (2023) reported nurse participants identifying negative impacts of the pandemic on many of their relationships including with patients, employers and their communities. They also described experiencing uncertainty and fear, emotional ramifications including feelings of isolation and feeling they were expendable.…”
mentioning
confidence: 99%
“…There have been many papers written about the effects of the pandemic on the nursing workforce (Jackson, 2022) and we are still in a place of learning from the changes and innovations instigated during the pandemic.However, we do know that nurses experienced many personal and professional stressors because of the COVID-19 pandemic. In a study that aimed to identify the impacts of the pandemic on nurses,Morley et al (2023) reported nurse participants identifying negative impacts of the pandemic on many of their relationships including with patients, employers and their communities. They also described experiencing uncertainty and fear, emotional ramifications including feelings of isolation and feeling they were expendable.…”
mentioning
confidence: 99%